Islamic Legal Reform In Facing The Challenges of The Digital Economy And The Islamic Financial System - Amrullah, Amrullah; Richard, Richard (Sekolah Tinggi Ilmu Syariah Wal Aqidah Ash-Shofa Manonjaya, 2026)
The development of the digital economy, including fintech, e-commerce, and Sharia-compliant digital assets, has created an urgent need for reform of Islamic law in regulating modern financial transactions. Although the basic principles of Islamic law, such as the prohibition of riba (usury), gharar (gharar), and maysir (risk of betting), as well as the provisions of Sharia contracts, serve as primary guidelines, practice demonstrates a gap between classical norms and the dynamics of the digital economy. The primary legal bases, namely the Qur'an (Qur'an, Surah Al-Baqarah: 275-279, Surah An-Nisa': 29) and the Hadith concerning buying and selling and contracts, are sometimes difficult to directly apply to digital instruments such as Sharia crowdfunding, digital tokens, and Sharia e-wallet services. Furthermore, fatwas issued by the National Sharia Council (DSN-MUI) and international standards such as AAOIFI and IFSB do not fully cover all financial technology innovations, creating legal uncertainty and challenges to Sharia compliance. Some digital transaction practices, such as the use of smart contracts, digital asset trading, and peer-to-peer lending, still require new interpretations to fulfill the principles of fairness, transparency, and equality in contracts. This research employs a normative juridical method with statutory regulations approach and Islamic legal concepts, utilizing secondary data from Islamic legal literature, national regulations, fatwas from the National Sharia Council (DSN-MUI), and AAOIFI and IFSB standards. The analysis aims to identify areas of Islamic law that must be updated or developed to accommodate innovations in the digital economy and the Islamic financial system. It also provides recommendations for regulators, academics, and practitioners in creating a digital financial ecosystem that is compliant with Islamic principles and legally secure.